Pediatric cancer patients undergoing amputation as a treatment for osteosarcoma (Research, Society and Development, 2022)
In the first analysis, it is worth noting that osteosarcoma is a cancerous pathology, characterized by progressive pain in the bones and sometimes in the soft parts, which can result in bone fractures. This disease has no specificity of groups of people for occurrence, but prevails in men, and the development of systemic symptoms is rare. Biopsy is the main test for diagnostic confirmation, with the aid of imaging tests. Treatment is based on chemotherapy, and surgical intervention to remove the tumor is also an option, depending on the case. Furthermore, amputation of the affected limb is sometimes indicated, assessing the severity of the situation. The clarification of the clinical picture for the family, as well as for the patient, is essential, and the importance of psychological follow-up should be emphasized. In view of this, there are cases of metastatic osteosarcomas, in which therapy is based only on palliative care, to relieve symptoms, offering dignity in coping with the health-disease process and thus, providing the patient with the best possible quality of life until the end of life. end of his days and supporting the family in the time of mourning.